Eleanor Oliphant is Completely Fine - Honeyman, Gail (London : Harper Collins, 2017)
"Smart, warm, uplifting, the story of an out-of-the-ordinary heroine whose deadpan weirdness and unconscious wit make for an irresistible journey as she realizes the only way to survive is to open her heart. Meet Eleanor Oliphant: she struggles with appropriate social skills and tends to say exactly what she's thinking. That, combined with her unusual appearance (scarred cheek, tendency to wear the same clothes year in, year out), means that Eleanor has become a creature of habit (to say the least) and a bit of a loner. Nothing is missing in her carefully timetabled life of avoiding social interactions, where weekends are punctuated by frozen pizza, vodka, and phone chats with Mummy. But everything changes when Eleanor meets Raymond, the bumbling and deeply unhygienic IT guy from her office. When she and Raymond together save Sammy, an elderly gentleman who has fallen on the sidewalk, the three become the kind of friends who rescue each other from the lives of isolation they have each been living. And it is Raymond's big heart that will ultimately help Eleanor find the way to repair her own profoundly damaged one"--
Costa First Novel Award, Shortlist 2017.
Keywords: Single women -- Fiction; Social isolation -- Fiction; Friendship -- Fiction